2020
DOI: 10.3390/ijerph17103471
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Better “Person–Environment Fit” through Items Calibration of the SIS-C

Abstract: The Supports Intensity Scale–Children’s Version (SIS-C) is the only available tool to assess extraordinary support needs for children and adolescents with intellectual disability. In past years, several works have proclaimed the need for its ongoing improvement as a measurement instrument. To contribute to this line of research, the goal of this work is to analyze the reliability of the SIS-C and its usefulness to distinguish between different levels of intensity of support needs. To address this, 814 children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…By stressing the interaction “person × environment”, the essential characteristic of the supports paradigm is that all people will present support needs since all people experience mismatches in certain situations and moments of their lives. The key is that the support needs of persons with IDD are extraordinary and extend beyond what most typically functioning people require to participate in the same contexts and activities [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…By stressing the interaction “person × environment”, the essential characteristic of the supports paradigm is that all people will present support needs since all people experience mismatches in certain situations and moments of their lives. The key is that the support needs of persons with IDD are extraordinary and extend beyond what most typically functioning people require to participate in the same contexts and activities [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the support needs construct in applying this paradigm has motivated the development of tools for its measurement. Although different approaches to measuring support needs exist, efforts are being made to develop standardized measures of the extraordinary support needs of persons with IDD based on the supports paradigm [ 15 , 16 ]. The advances in the measurement of extraordinary support needs have been evident [ 17 ], but performing a support needs assessment with psychometric instruments poses challenges that are yet to be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, its application procedures have been discussed, as well as the validation of its measurement model and its generalization among groups of individuals. Recent research also identified a ceiling effect on the scale and warns about the difficulty of its use in people with greater support needs [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%